2007
DOI: 10.1007/s11661-007-9305-4
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Grain Rotation and Roping of Stainless Steel

Abstract: The recent application of crystal plasticity calculations to electron backscatter diffraction (EBSD) data from ferritic stainless steel sheet has confirmed the presence of grain clusters parallel to the rolling direction (RD) with similar deformation tendencies. The results of these simulations provide strong support for the Takechi model of roping. The remaining question that has not yet been adequately addressed is how the deformation tendencies of grains/grain clusters are affected by being embedded within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…The terms ‘roping’ and ‘ridging’ refer to the surface appearance of the material that shows rope-like features parallel to the prior rolling direction and distributed along the transverse direction. This phenomenon was observed in ferritic stainless steels [ 1 , 2 ] as well as aluminum alloys [ 3 , 4 ]. Both materials are often used for exterior applications whose surface appearance is important (e.g., automotive body applications).…”
Section: Introductionmentioning
confidence: 92%
“…The terms ‘roping’ and ‘ridging’ refer to the surface appearance of the material that shows rope-like features parallel to the prior rolling direction and distributed along the transverse direction. This phenomenon was observed in ferritic stainless steels [ 1 , 2 ] as well as aluminum alloys [ 3 , 4 ]. Both materials are often used for exterior applications whose surface appearance is important (e.g., automotive body applications).…”
Section: Introductionmentioning
confidence: 92%
“…Grains having a strong shearing tendency were embedded within a matrix having either a strong opposite shearing tendency or no shearing tendency. From these simulations it was shown that the tendency for shearing in orientations such as {1 1 1} 1 1 0 was far stronger than the tendency for no shearing in grains having orientations such as {1 1 1} 1 1 2 , this result being explained by the difference in the slope of Taylor factor with respect to shear component of the deformation gradient [13]. These results indicated that the grains having no net tendency for shearing would shear if placed adjacent to grains having a strong shearing tendency, thereby increasing the number of grains contributing to the net shearing behaviour.…”
Section: Introductionmentioning
confidence: 96%
“…It is known empirically, however, that the microstructure through the sheet thickness has a significant effect on the characteristics of roping. In an attempt to specifically look at the importance of local environment on the tendency for individual grains to shear, Sinclair [13] used the VPSC code with idealized microstructures to study the deformation behaviour of individual grains embedded within different media. Grains having a strong shearing tendency were embedded within a matrix having either a strong opposite shearing tendency or no shearing tendency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such bands are believed to originate from the as‐cast columnar grains with {001}〈uv0〉 orientations, which persist even after numerous processing steps 4–6. There is now a general consensus that the out‐of‐plane shear rate model put forward by Takechi et al 8 and later validated by others 5, 7, 9, 10 is the most likely mechanism of ridging in the presence of a banded orientation distribution.…”
Section: Introductionmentioning
confidence: 97%